Clinical outcome analysis of intramural myoma greater than 8 cm in diameter removed during caesarean section: a retrospective study - Chunbo Shi; Jinliang Chen; Aner Chen (BMC, 2023)
Abstract Objective To explore the safety and efficiency of endometrial myomectomy (EM) and Serosal myomectomy (SM) for the removal of intramural myoma greater than 8 cm in diameter during cesarean section. Methods Retrospective analysis and follow-up were used, and 190 cases of pregnancy complicated with uterine myoma from Jan. 2017 to May 2022 in Ningbo Women's and Children's Hospital were collected, 130 cases of caesarean myomectomy as study group, 64 cases of EM as study group A, 66 cases of SM as study group B, 33 cases with uterine fibroids removed before suturing the uterine incision as study group B1, 33 cases with uterine incision sutured followed by removal of fibroids as study group B2, 60 cases of Caesarean section alone as control group. To compare perioperative conditions between and within groups. Results ① Operation time, postoperative exhaust time, pre- and post-operative haemoglobin drop, intraoperative blood loss were all more than those of the control group in the study group (68.65 ± 11.87 vs 56.17 ± 9.18 min, 21.04 ± 4.98 vs 17.03 ± 1.3 h, 1.27 ± 0.59 vs 1.09 ± 0.43 g/dl, 613 ± 221 vs 532 ± 156 ml, P < 0.001, P < 0.001, P = 0.025, P = 0.011). ② For type III and V fibroids, the time of myoma removal, postoperative exhaust and pre- and post-operative haemoglobin drop and intraoperative blood loss in study group A were less than those in study group B (18.02 ± 3.89 vs 20.19 ± 5.32 min, 18.83 ± 2.57 vs 23.93 ± 6.84 h, 600 ± 194 vs 730 ± 277 ml, 1.20 ± 0.57 vs 1.59 ± 0.70 g/dl, P = 0.036, P < 0.001, P = 0.014, P = 0.008); For type IV uterine fibroids, only postoperative exhaust time was less in Study Group A than in Study Group B (19.27 ± 2.2 vs 21.35 ± 3.23 h, P = 0.016). ③ Time of myoma removed was less in study group B1 than in study group B2 (18.24 ± 4.53 vs 20.7 ± 4.59 min, P = 0.033). Conclusion It is safe and feasible to remove interstitial myomas larger than 8 cm in diameter during caesarean section. EM has the advantage of shorter operation time and less intraoperative bleeding, SM, in a way that the myoma is removed before suturing the uterine incision, can shorten the myomectomy time. It can benefit the patients more.